Determination of Effective Delay-Avoidance Practices in Construction Projects - Vacanas, Yiannis; Danezis, Chris (My University, 2021)
Delay poses a significant issue for the worldwide construction industry and national economies. Numerous research endeavors have been carried out to shed light on the sources of delay, among which some employ statistical approaches to consider the perceptions of the industry's main stakeholders. However, only a few suggest practices for delay mitigation but without considering their importance as perceived by the involved parties, which is crucial for appreciating their acceptance by the stakeholders and assess their immediate applicability. This research proposes an integrated statistical approach to determine the main delay sources, and identify the most effective, commonly accepted practices to promote delay mitigation. The perception of stakeholders was investigated via parametric and nonparametric methods. The results showed that, although there is an a priori disagreement in the perception of each party with respect to delay responsibility, commonly accepted delay mitigation practices can be successfully identified and thereby proposed.
Keywords: Construction; Cyprus; Delay; Delay avoidance; Delay mitigation; Measures; Project management